2017
DOI: 10.1111/cla.12187
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic diversification history with rate upshifts in Holarctic bell‐flowers (Campanula and allies)

Abstract: Campanula s.l. is one of the most speciose flowering plant lineages of the Holarctic (ca. 600 species). In the present study we sequenced three regions of the plastid genome (petD, rpl16 and trnK/matK) across a broad sample of Campanula s.l., which markedly improved phylogenetic resolution and statistical support compared to previous studies. Based on this robust phylogenetic hypothesis we estimated divergence times using BEAST, diversification rate shifts using Bayesian Analysis of Macroevolutionary Mixture (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 124 publications
1
27
0
Order By: Relevance
“…() was caused by using an invalid likelihood function. Considering the ongoing debate, we ran a number of separate B amm analyses, an approach that was also recently used in Campanula (Jones et al ., ). We initially conducted an analysis with the prior set as 1 for the ‘ExpectedNumberofShifts’ as suggested for small trees (< 500 tips).…”
Section: Methodsmentioning
confidence: 97%
“…() was caused by using an invalid likelihood function. Considering the ongoing debate, we ran a number of separate B amm analyses, an approach that was also recently used in Campanula (Jones et al ., ). We initially conducted an analysis with the prior set as 1 for the ‘ExpectedNumberofShifts’ as suggested for small trees (< 500 tips).…”
Section: Methodsmentioning
confidence: 97%
“…However, Rabosky et al [ 48 ] demonstrated that the conclusion of Moore et al [ 47 ] resulted from an invalid likelihood function, and suggest that in the most recent version of BAMM (v.2.5), the extreme sensitivity to the prior cannot be replicated. Considering this ongoing debate, we performed multiple BAMM analyses, similar to previous studies of Campanula [ 49 ] and Theaceae [ 11 ], by using various prior values (0.5, 1, 2, 5, and 10) to determine whether our results were affected by different prior settings.…”
Section: Methodsmentioning
confidence: 99%
“…To date, little was known concerning the evolutionary relationships within this group. Although past studies (e.g., Mansion & al., 2012;Jones & al., 2017) provided preliminary evidence of the polyphyly of C. sect. Quinqueloculares, our results offer the first comprehensive phylogenetic framework that includes a complete taxon sampling and 10 molecular markers.…”
Section: ■ Conclusionmentioning
confidence: 99%